HISTORY OF FERGANA VALLEY POTTERY (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article contains information about pottery, which is one of the types of applied folk art, the branch of crafts that makes various items, dishes, and building materials from clay. Theoretical and practical information about the history of pottery development in the valley, its schools and centers, as well as transformational processes and modifications, is widely and comprehensively covered.